ТHE TRANSFORMATION CONCEPTION OF PRICING IN CONDITIONS OF GLOBALIZATION OF ECONOMY - О. П. Чукурна (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2015)
In the article are considered the factors of influence of globalization on transformation of conception of pricing. It is analyses features of processes of globalizations that influence on development of economy. The factors of influence of globalization are certain on transformation of conception pricing it is attributed to that: international competition and transaction charges. Nature of transaction charges and their direct influence are described on the transfer pricing. The basic methods of the transfer pricing are certain, as one of the newest approaches in relation to conception of price. The mechanism of favorable tax treatment is considered at the transfer pricing. Basic advantages and certain defects of the transfer pricing and influence of his mechanism are analyses to the market and administrative levers. The theories of global markets that influenced on transformation of conception of pricing are set forth, most reasonable among that are the following: theory of internationalization, theory of appropriation, tax theory.